The STRENGTHENING THE ROLE OF CUSTOMARY VILLAGES IN SPIRITUAL TOURISM MANAGEMENT IN BALI - I Nyoman Surpa Adisastra; Bagus Ade Tegar Prabawa (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
Abstract Spiritual tourism is becoming one of the trends in Bali. Many people are currently promoting spiritual tourism. Starting from the private sector as well as under the management of tourist villages or customary villages. One of the popular ones is melukat, which is generally done by bathing in a water source that they consider sacred. Although spiritual tourism has been managed and supervised, it sometimes comes with risks. There have been several instances of visitors breaking the rules in sacred places. For example, they were climbing onto a pelinggih (shrine). Customary villages in Bali have the authority to manage and develop tourist villages through Baga Utsaha Padruwen Desa Adat (BUPDA). As with official villages, customary villages can manage tourist villages by utilizing the potential of their area. One of them is spiritual tourism. In terms of regulations, the Bali Provincial Government has tried to provide a legal umbrella related to tourism management to customary villages. However, this is not enough. Customary villages, both in terms of institutions and communities, can strengthen their role if they can manage tourist attractions in their area. One of the important things in this case is the formation and strengthening of the quality of Human Resources (HR). In spiritual tourism management, customary villages need to have reliable human resources. Of course, to procure quality human resources requires a lot of money. Especially if recruiting professionals in their fields. However, following the spirit of gilik-saguluk (togetherness), salunglung sabayantaka (cooperation), and sareng-sareng (participation) owned by indigenous villages, quality human resources can be formed through the empowerment of krama (community members) of indigenous villages who can manage tourism, based on education and experience. On the other hand, some cases involving visitors to sacred places in Bali are certainly detrimental to customary villages, both institutionally and as a community. This relates to the impact caused, when inappropriate things are done in sacred places, for example climbing or sitting on pelinggih, doing damage, and so on. Although the customary village has made efforts to supervise cases have recurred. Therefore, customary villages or managers cannot work alone in terms of this supervision. The involvement of security forces is needed. The customary village already has pecalang who is in charge of security. However, pecalang must also be supported through training by involving related institutions, such as the police. This research addressed three issues: 1) How is the authority of customary villages in Bali in the management of tourism in the region? 2) How is the strategy to strengthen the role of customary villages in the management of spiritual tourism? 3) What are the efforts of customary villages in monitoring spiritual tourism in their area? The purpose of writing the article is to examine the authority of customary villages in tourism management, strengthening the role of customary villages in spiritual tourism management, and supervision of spiritual tourism in their area. The method used is qualitative through a literature research. Data is collected from previous literature that discusses spiritual tourism and the role of customary villages and then analyzed. Keywords: spiritual tourism, customary village, Hinduism